It's in Our Blood: Indigenous women's knowledge as a critical path to women's well-being - Gaudet, Janice Cindy; Caron-Bourbonnais, Diane (AlterNative: An International Journal of Indigenous Peoples, 2015)
The research reported in this article sought to shed light on the North, Central and South American indigenous moon time teachings related to the menstrual cycle of women. The historical institutionalization, medicalization and colonization of indigenous women's practices have devalued and almost destroyed this knowledge. This study explored the question of whether or not lost indigenous knowledge of women's power can be reclaimed for women's health and well-being. A qualitative participatory research methodology was adopted, based on an indigenous paradigm and scholarly rigour and including protocols acceptable to an Ojibwe grandmother, Isabelle Meawasige, who shared her knowledge and experience. The experiential knowledge gained and the meanings expressed by female participants in a circle sharing facilitated by the principal author are presented and discussed. The results of this research reveal optimistic possibilities to co-create health and well-being for the participants, grounded in what is both visible and invisible within indigenous women's culture.
Keywords: amériques; approches et analyses; care; cours; cycle menstruel; discipline; féminisme autochtone; justice reproductive; médecine; médicalisation; pol4105; premier cycle; règles; régions géographiques; santé; sciences; sciences de la santé; sciences humaines; système colonial; systèmes d'oppressions; thématiques; travail social

Trauma and recovery: The aftermath of violence, from domestic abuse to political terror - Herman, Judith Lewis (Basic Books, 2015)
Lorsque Trauma and Recovery a été publié pour la première fois en 1992, il a été salué comme un travail révolutionnaire. Au cours des années intermédiaires, le volume de Herman a changé la façon dont nous pensons et traitons les événements traumatisants et les victimes de traumatismes. Dans une nouvelle postface, Herman raconte l'incroyable réponse que le livre a suscitée et explique comment les problèmes entourant le sujet ont changé au sein de la communauté clinique et de la culture en général. Traumatisme et récupération apporte un nouveau niveau de compréhension à un ensemble de problèmes généralement considérés individuellement. Herman s'appuie sur ses propres recherches de pointe sur la violence domestique ainsi que sur la vaste littérature des vétérans de combat et des victimes de la terreur politique, pour montrer les parallèles entre les terrorismes privés tels que le viol et les traumatismes publics tels que le terrorisme. Le livre met l'expérience individuelle dans un cadre politique plus large, arguant que le traumatisme psychologique ne peut être compris que dans un contexte social. Méticuleusement documenté et utilisant fréquemment les propres mots des victimes ainsi que ceux des œuvres littéraires classiques et des journaux de prison, Trauma and Recovery est un travail puissant qui continuera à avoir un impact profond sur notre pensée
Keywords: abus sexuels; cours; discipline; enfance; médecine; psychiatrie; terrorisme; thématiques; traumatismes; trs3500; violences; violences conjugales; violences sexuelles